Analysis of Ion and Dissolved Organic Carbon Interference on Soil Solution Nitrate Concentration Measurements Using Ultraviolet Absorption Spectroscopy. Issue 12 (19th December 2014) - Shaw, B.D.; Wei, J.B.; Tuli, A.; Campbell, J.; Parikh, S.J.; Dabach, S.; Buelow, M.; Hopmans, J.W.
Abstract : Nitrate is often present in surface water, soil solution, and groundwater at undesirable or toxic levels. This study follows development of an in situ nitrate monitoring probe and examines its performance in the presence of potentially interfering ionic species and dissolved organic carbon (DOC). Ultraviolet (UV) absorption spectroscopy measurements of aqueous NO3 − were obtained under conditions where prevalent ionic species (i.e., Na +, K +, Ca 2+, Mg 2+, NH4 +, Zn 2+, Cu 2+, Mn 2+, Fe 2+, Fe 3+, Al 3+, Cl −, H2 PO4 −, HPO4 2−, SO4 2−, and HCO3 − ) and DOC were present at maximum characteristic concentrations for a range of pH levels, allowing UV interference on NO3 − concentrations from individual ions to be investigated. While most solutions did not show interference, Fe 2+ ions and DOC absorbed ultraviolet light strongly in regions of the spectrum where NO3 − also exhibited significant absorption. Natural water samples showed very low concentrations of Fe 2+, which do not cause interference with nitrate measurements. A two‐wavelength measurement scheme was adopted to correct for the potential interference of DOC in measurements of aqueous NO3 − . A multivariate calibration is presented to account for possible interference from both DOC and other ions in solution. The application of the UV spectroscopy probe is especially useful for deep vadose zone measurements of nitrate, as typically DOC concentrations will exponentially decrease with depth, and ion interference will be low.